The Effect of Effleurage Massage on Primary Dysmenorrhea in Female Adolescent Students - Nur Rahmawati Sholihah; Imroatul Azizah (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
Primary dysmenorrhea is a painful condition during menstruation. It is characterized as cramping and is centered on the lower abdomen. The state may be accompanied by headaches, nausea, vomiting, diarrhea, and mild to severe trembling as it affects daily activities. The dysmenorrhea condition would affect the quality of life of most women. This study aimed to determine the effect of effleurage massage on primary dysmenorrhea of female adolescents in student’s dormitory of General Achmad Yani University, Yogyakarta. Method This research used a quasi-experimental approach with pre and post-test for two-group design. A total sample of 58 respondents was divided into the intervention and control groups. The sample determination used simple random sampling. Furthermore, the data is analyzed using the Wilcoxon test. Results this research showed a significant difference between the intervention groups and the control group was found after the intervention group was given the effleurage massage treatment (p <0.05). The conclusion of this research is effleurage massage has a significant effect on reducing pain in the lower abdomen during menstruation (dysmenorrhea). It is recommended to promote effleurage massage as an alternative to non-pharmacological treatment for female adolescents to reduce pain due to their dysmenorrhea.